Effect of Workstation Type on the Relationship Between Fatigue, Physical Activity, Stress, and Sleep. Issue 3 (March 2021) - Goel, Rahul; Pham, Alan; Nguyen, Hung; Lindberg, Casey; Gilligan, Brian; Mehl, Matthias R.; Heerwagen, Judith; Kampschroer, Kevin; Sternberg, Esther M.; Najafi, Bijan
Abstract : Objective: This study examined office workstation types' impact on the relationship between fatigue and three health metrics: physical activity, stress, and sleep quality. Methods: Data from 225 office workers were collected for perceived fatigue, perceived sleep quality (Pittsburgh Sleep Quality Index [PSQI]), physiological stress response (standard deviation of heart rate variability [HRV]), and physical activity (total activity in minutes) during three consecutive workdays. Stress and physical activity were measured using chest-worn sensors. Workers were then categorized as tired or not-tired based on the median of the fatigue rating. Results: Among tired workers, open-bench seating workers had increased physical activity, improved sleep quality, and reduced stress compared with workers in private offices and cubicles. Conclusions: Office workstation types influence physical activity and levels of stress during work hours, which in turn affect sleep quality.